Energy, CO2, and AQI Efficiency and Improvement of the Yangtze River Economic Belt - Fang-Rong Ren (Energies, 2019)
With the rapid development of its economy, environmental governance is becoming more important in China. The Yangtze River Economic Belt (YREB), as the world’s largest inland shipping channel, can lead the country’s regional green economy development. As most research on China’s environmental efficiency focuses on provinces or the east and west regions, this paper examines its energy input and output and environmental effects from the aspects of YREB and non-YREB, breaking through the limitations of previous studies that only used cross-section or panel data for environmental assessment. This paper employs the meta-frontier dynamic SBM model, selects fixed assets as carry-over indicators, and considers the interrelationships between the dynamics variables during 2014⁻2016. The results are as follows: The overall energy efficiency and CO2 emission efficiency of YREB are higher than those of non-YREB. The difference in energy consumption, CO2, and AQI efficiency is large, but the performance of YREB is generally better than that of non-YREB. After setting the meta-frontier, non-YREB is better than YREB, for the main reason that the technology gap values of YREB are smaller than those of non-YREB. Our findings thus suggest that YREB should strengthen technical exchanges and promotion within its region, thereby decreasing regional technology differences, while non-YREB should address environment protection and CO2 emissions and advocate a low-carbon production mode.